Technology Acceptance Model for the Use of Learning Management System in Indonesia - Graha Prakarsa; Elly Komala (Sainteks: Jurnal Sain dan Teknik, 2023)
This research is based on a problem, mainly that there has been an increase in the usage of learning management systems, necessitating the use of TAM for evaluating user acceptance. This research is categorized as quantitative research using Partial Least Squares – Structural Equation Modelling (PLS-SEM) technique method. Data collection technique were obtained through online questionnaires involved 100 respondents of Learning Management System (LMS) users. The questionnaires were assembled based on 21 instruments which were indicators in this study. The results shows that compatibility does not have a significant effect on perceived usefulness, but it has a significant impact on perceived ease of use. Perceived ease of use has a significant influence on perceived usefulness. Perceived service quality and perceived usefulness have an effect on behavioral intention while perceved ease of use does not have an impact on behavioral intention. Perceived usefulness was simultaneously affected by 50.2%, perceived ease of use was affected with 10.8%, and the behavioral intention variable was simultaneously influenced by 19.2%.